Formulation and Charecterization and Evaluation Gentamicin Sulphate and Loratadine Emulgel for Treatment as Anti-Bacterial and Anti-Allergic - Ansari, Abdul Haque; Mishra, Ankit Kumar; Mishra, Jai Narayan (Journal of Neonatal Surgery, 2025)
This research focuses on developing a topical emulgel system formulation combining Gentamicin sulphate aminoglycoside (an antibiotic and allergic agent) to enhance the better treatment of localized skin infections and allergic reactions. Loratadine H1 receptor (an anti-allergic). Emulgel, a hybrid novel system of emulsion and gel, allows for effective delivery of both hydrophilic waters loving nature and hydrophobic drugs while bypassing the gastrointestinal tract and first-pass metabolism in the formulation offers several many type advantages, including improved patient compliance, enhanced skin penetration, better stability, thixotropy, High Spredaability, and non-greasy texture. Pre-formulation studies assessed the compatibility and solubility of both drugs, Gentamicin Sulphate and Loratadine along with physicochemical properties like pH, melting point, TLC, Particle size, flowability, as angle of repose, bulk tapped density and FTIR analysis. Emulgel was prepared using Carbopol grade as a gelling agent, Span 20 and Tween 20 as emulsifiers, and preservatives like methyl and propyl parabens. Triethanolamine pH adjuster, Evaluation studies included organoleptic assessment, rheology, in vitro drug release, zeta potential, SEM imaging, skin irritation tests, and stability studies. The dual-drug combination aims to provide desired therapeutic effects against bacterial infections and allergic inflammation, overcoming solubility limitations and ensuring better topical absorption. This research supports the development of an effective dermatological treatment with improved clinical outcomes and patient convenience. This research demonstrates that combining Gentamicin and Loratadine in an emulgel base not only enhances their individual therapeutic potentials but also ensures patient compliance, localized action, and reduction of systemic side effects. The findings support the potential of this dual-drug emulgel as a promising alternative in dermatological therapy, offering improved outcomes for patients with concurrent skin infections and allergic responses.